Non-competition interests in EU antitrust law : an empirical study of Article 101 TFEU - Brook, Or, 1985- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
This book is the first to empirically examine the role of non-competition interests (public policy) in the enforcement of the EU's prohibition on anti-competitive agreements. Based on an original quantitative and qualitative database of over 3,100 cases, this book records all of the public enforcement actions of Article 101 TFEU taken by the Commission, EU Courts, and the national competition authorities and courts of five representative Member States (France, Germany, Hungary, the Netherlands, and the UK). The book not only exposes explicit tools in which non-competition interests played a role, but also sheds light on the "dark matter" of balancing, namely, invisible forms of balancing triggered by the institutional and procedural setup of the competition enforcers. Moreover, it contributes to the empirical-legal study of various other aspects of EU competition law enforcement, such as its objectives, the more economic approach, decentralized enforcement, and the functioning and success of Regulation 1/2003.
Introduction and methodology -- History of Article 101 TFEU -- Article 101(3)TFEU individual exemptions -- Block exemptions regulations -- Article 101(1)TFEU -- National balancing tools -- Enforcement discretion -- Conclusion.
Title from publisher's bibliographic system (viewed on 10 Jun 2022).
Keywords: Treaty Establishing the European Economic Community -- (1957 March 25).; Antitrust law -- European Union countries